Development of an Anti-Bullying Pocket Book Cua Meci Angi Based on Local Wisdom Values of Maja Labo Dahu for Elementary School Students - A. Gafar Hidayat; Tati Haryati; Taufik, Taufik (JURNAL PENDIDIKAN IPS, 2024)
Development of an Anti-Bullying Pocket Book "Cua Meci Angi" and "Maja Labo Dahu" as an Effort to Prevent Bullying in Elementary Schools. "Cua Meci Angi" signifies mutual love and respect. The objectives of this study were: 1) to describe the stages of developing an anti-bullying pocket book; 2) to analyze the feasibility of the anti-bullying pocket book; and 3) to analyze the practicality of the anti-bullying pocket book. The research method used was Research and Development (R&D) using the 4D model. The product was developed through four stages: 1) Definition; 2) Design; 3) Development; and 4) Dissemination. The developed anti-bullying pocket book "Cua Meci Angi" can be used as a guide for students, teachers, and parents. The results showed that the product was highly valid, with an average score of 92.72% for content, 97.77% for language, and 94.47% for design. It was deemed suitable for use. The results of the practicality and effectiveness test of the product on students (94.6%), teachers (90.79%), and parents (91.74%) showed that the developed product can provide understanding about the prevention, handling, and punishment of bullying behavior in school environments by prioritizing local wisdom values.